Crystal structure and topological affinities of magbasite, KBaFe3+Mg7Si8O22(OH)2F6: a trellis structure related to amphibole and carpholite. (February 2014) - Welch, M. D.; Mitchell, R. H.; Kampf, A. R.; Chakhmouradian, A. R.; Smith, D.; Carter, M.
Abstract: The crystal structure of magbasite from the Eldor carbonatite complex, Quebec, Canada, has been determined and indicates that the currently accepted formula should be revised to KBaFe 3+ Mg7 Si8 O22 (OH)2 F6 . Magbasite is orthorhombic, space group Cmme ( Cmma ), with unit-cell parameters a 18.9506(3) Å, b 22.5045(3) Å, c 5.2780(1) Å, V 2250.93(6) Å 3 ( Z = 4). The structure has been solved and refined to final agreement indices R 1 = 0.026, wR 2 = 0.052, GooF = 1.116 for a total of 2379 unique reflections, and is a new kind of trellis motif related to amphibole and carpholite topologies. An amphibole-like I-beam ‖(100) of edge-sharing octahedrally-coordinated M (1, 2, 3) sites, which are filled by Mg, is sandwiched between double-chains of SiO4 tetrahedra ‖c. This I-beam is connected to side-ribbons ‖(010) of edge-sharing (Mg, Fe 2+ )O4 (OH, F)2 and Fe 3+ O4 (OH)2 octahedra to form a tunnelled box or trellis structure very like that of carpholite, for which the I-beams are pyroxene-like. K occupies a tunnel site analogous to the A site of amphibole. Ba occupies a cavity site at the corners where the I-beam and side-ribbon meet, and corresponds to the A site of carpholite. The structural relations between magbasite and carpholite are discussed.